2020
DOI: 10.1108/ijoa-11-2019-1923
|View full text |Cite
|
Sign up to set email alerts
|

Servant leadership and academics outcomes in higher education: the role of job satisfaction

Abstract: Purpose The purpose of this paper is to investigate the impact of servant leadership on work engagement and affective commitment among academics in higher education. Moreover, the paper highlights the role of job satisfaction as an intervening mechanism among the examined variables. Design/methodology/approach Self-administered questionnaires were distributed to academics working in the Palestinian higher education sector. We used structural equation modelling to examine the hypotheses. Findings A positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 84 publications
(102 citation statements)
references
References 127 publications
4
91
0
7
Order By: Relevance
“…Our study addresses recent calls for research to understand better how psychological well-being influence employees' performance at work (Huang et al, 2016), and adds to a growing body of work, which confirms the importance of psychological well-being in promoting work-related attitudes and behaviors (Devonish, 2016;Hewett et al, 2018;Ismail et al, 2019). Further, we have extended the literature on employee affective commitment, highlighting that psychological well-being is an important antecedent of employee' affective commitment and thereby confirming previous research by Aboramadan et al (2020) on the links between affective commitment and job performance.…”
Section: Theoretical Implicationssupporting
confidence: 84%
“…Our study addresses recent calls for research to understand better how psychological well-being influence employees' performance at work (Huang et al, 2016), and adds to a growing body of work, which confirms the importance of psychological well-being in promoting work-related attitudes and behaviors (Devonish, 2016;Hewett et al, 2018;Ismail et al, 2019). Further, we have extended the literature on employee affective commitment, highlighting that psychological well-being is an important antecedent of employee' affective commitment and thereby confirming previous research by Aboramadan et al (2020) on the links between affective commitment and job performance.…”
Section: Theoretical Implicationssupporting
confidence: 84%
“…These results are also supported by Harris et al (2016), who demonstrated that SL promotes JS and enhances retention. Aboramadan et al (2020) investigated the role of JS in the relationship between SL and academic performance and found that JS fully mediated this relationship, which means that SL affects JS, which in turn enhances the academic performance of schools. Likewise, researchers from different fields have found that SL in an institution affects the school climate, student performance, retention and JS (Al-Mahdy et al, 2016;Anderson, 2005;Black, 2010;Cerit, 2009;Gary, 2017;McCann et al, 2014;Miears, 2004;Thompson, 2003), all of which are crucial factors for the education system.…”
Section: Relationship Between Sl and Jsmentioning
confidence: 99%
“…In an effort to bridge this gap in the literature, researchers started building on the relationship between SL and attitudinal work variables such as organizational commitment (Aboramadan et al , 2020a, 2020b; Dahleez and Ghali, 2018; Keith, 2015; Liden et al , 2014b; Pierro et al , 2013; VanMeter et al , 2016). Further, Jackson et al (2013), in a meta-analysis, stressed that organizational commitment is one of the most significant outcomes of effective leadership practices.…”
Section: Introductionmentioning
confidence: 99%